Mechanical milling of the intermetallic compound AlFe - Meyer, Marcos (1999)
The intermetallic compound AlFe in its ordered B2 phase has been ground under Ar in a ball-milling device. The system evolution under mechanical work has been examined as a function of time of milling by x-ray diffraction, transmission Mossbauer spectroscopy, and differential scanning calorimetry. Short and long range disorder was observed. The evolution of the long range order parameter with milling time is analyzed up to the completion of the solid state reaction when a steady state value is reached. The short range order evolution is consistent with a nonstatistical order distribution throughout the sample but mainly distributed in two regions with different degrees of order each. Kinetic analysis of the reordering and recrystallization has been per- formed under continuous heating and isothermal calorimetric regimes. Modeling of these processes is pre- sented as well as the estimated values of both the enthalpy and the activation energy of the reordering process. Results are compared with preceding information on related systems.